Kemampuan guru dalam mengembangkan perencanaan pembelajaran terintegrasi: Studi kasus penguatan pendidikan karakter, 4C, literasi, dan HOTS - Hayati, Dwi (Aksara: Jurnal Bahasa dan Sastra, 2023)
The objectives of this school action research are: (1) describing the improvement of the Training Guidance process in improving the ability of teachers to develop learning planning by integrating PPK, 4C, Literacy and HOTS and (2) describing the improvement of teachers' abilities in developing integrated learning planning PPK, 4C, Literacy, and HOTS through training guidance and joint studies at SMPN 24 Bandar Lampung in semester 2 of the 2022/2023 Academic Year. This study was conducted with the subjects of the study of 24 teachers. This research is a school action research with research steps of planning, acting, observing, and reflecting. The implementation of actions is carried out as many as two cycles, each cycle is carried out 2 meetings.The results of the study are as follows: (1) there is an increase in proses training guidance in learning planning development research by integrating PPK, 4C, Literacy and HOTS at SMPN 24 Bandar Lampung in semester 2 of the 2022/2023 academic year from cycle I to cycle II. There is an increase in the ability of teachers to develop integrated learning planning for PPK, 4C, Literacy, and HOTS through the training guidance process, which is 19.37 (33.04%) from the initial condition of the average score of 58.63 increased to 70.50 at the end of cycle I action, and increased again to 78.00 at the end of cycle II action. Thus, it can be concluded that by improving the process of training guidance and joint studies, it is proven to improve the ability of teachers to develop integrated learning planning for PPK, 4C, Literacy, and HOTS at SMPN 24 Bandar Lampung Semester 2 of the 2012/2013 Academic Year.Keywords: Ability, Bimlat, PPK, 4C, Literacy, HOTS Keywords: Ability, Bimlat, PPK, 4C, Literacy, HOTS